Evaluation of the friction force generated by monocristalyne and policristalyne ceramic brackets in sliding mechanics - Roberta Ferreira Pimentel; Roberto Sotto Maior Fortes de Oliveira; Maria das Graças Afonso Miranda Chaves; Carlos Nelson Elias; Marco Abdo Gravina (Dental Press Editora, 2013)
OBJECTIVE: To evaluate and compare "in vitro" the maximum friction force generated by three types of esthetic brackets, two types of polycrystalline conventional ceramic brackets (20/40 and InVu) and one type of sapphire monocrystalline bracket (Radiance) in dry and artificial saliva wet settings. Also, to evaluate the influence exerted by artificial saliva on the friction forces of those brackets. METHODS: Tests were performed in dry and artificial saliva wet setting (Oral Balance) by using an EMIC DL 10000 testing machine, simulating a 2 mm slide of 0.019 x 0.025-in rectangular stainless steel wires over the pre-angulated and pre-torqued (right superior canine, Roth prescription, slot 0.022 x 0.030-in) brackets (n = 18 for each bracket). In order to compare groups in dry and wet settings, the ANOVA was used. For comparisons related to the dry versus wet setting, the student t test was used for each group. RESULTS: The results showed that in the absence of saliva the Radiance monocrystalline brackets showed the highest friction coefficients, followed by the 20/40 and the InVu polycrystalline brackets. In tests with artificial saliva, the Radiance and the 20/40 brackets had statistically similar friction coefficients and both were greater than that presented by the InVu brackets. The artificial saliva did not change the maximum friction force of the Radiance brackets, but, for the others (20/40 and InVu), an increase of friction was observed in its presence. CONCLUSION: The InVu brackets showed, in the absence and in the presence of saliva, the lowest friction coefficient. OBJETIVO: avaliar e comparar in vitro as cargas máximas de atrito geradas por três tipos de braquetes estéticos, sendo dois deles cerâmicos policristalinos convencionais (20/40 e InVu) e um monocristalino de safira (Radiance), em ambientes seco e umedecido por saliva artificial. Também avaliar a influência exercida pela saliva artificial sobre as cargas de atrito dos referidos braquetes. MÉTODOS: os ensaios foram realizados em ambiente seco e em ambiente umedecido com saliva artificial em gel (Oral Balance), utilizando uma máquina de ensaios mecânicos (EMIC, modelo DL10000), simulando um deslizamento de 2mm de fios retangulares 0,019" x 0,025" de aço sobre os braquetes (n = 18, para cada braquete), pré-angulados e pré-torqueados (canino superior direito prescrição Roth, slot 0,022" x 0,030"). Para comparação entre os braquetes, em ambiente seco ou umedecido, utilizou-se a análise de variância; e para a comparação dos braquetes em ambiente seco e umedecido, utilizou-se o teste t para amostras independentes. RESULTADOS: os resultados obtidos indicaram que, na ausência de saliva, os braquetes monocristalinos Radiance demonstraram o maior coeficiente de atrito, seguidos pelos braquetes policristalinos 20/40 e InVu. Nos ensaios realizados em ambiente umedecido, os braquetes Radiance e 20/40 apresentaram coeficientes de atrito estatisticamente semelhantes, e superiores ao apresentado pelos braquetes InVu. A saliva artificial não promoveu alterações na força máxima de atrito para os braquetes Radiance; todavia, para os demais (20/40 e InVu), promoveu aumento significativo nos coeficientes de atrito. CONCLUSÃO: os braquetes InVu apresentaram, tanto nos ensaios realizados na ausência, quanto na presença de saliva, os menores coeficientes de atrito, entre os braquetes ensaiados.